Structural requirements for DNA binding of GCM proteins - Wegner, Michael; et al. (Nucleic Acids Research, 1998)
Members of the GCM family of transcription factors contain a DNA binding domain unrelated to any other known DNA binding domain and bind to a DNA sequence motif not recognized by any other known transcription factor. Here we show that positions 2, 3, 6 and 7 of the 5'-ATGCGGGT-3' motif are particularly important for DNA binding and that methylation of several G residues on the upper strand, but not on the lower strand, interfered with binding of GCM proteins. No differences were detected between the DNA binding of Drosophila GCM and mammalian mGCMa. Alanine scan mutagenesis of the DNA binding domain of mGCMa identified the three conserved amino acids K74, C76 and C125 as being essential for DNA binding. Conserved cysteine residues were also found to be important for maintaining the overall integrity of the DNA binding domain and for mediating redox sensitivity of DNA binding. These cysteine residues are arranged in a symmetrical structure that bears no resemblance to other cysteine-containing structures, such as zinc fingers. In agreement with this, DNA binding of mGCMa was not dependent on zinc ions. Our results give insights into the exact nature of the GCM binding sites expected in target genes and point to a role for redox regulation in the function of GCM proteins.
UnivIS-Import:2015-03-05:Pub.1998.med.IB.LPCIPDBI.struct